Propuesta para el aprovechamiento de residuos sólidos vegetales de la plaza de mercado “La Gran Plaza Campesina” de Suba Compartir a través del sistema de lombricultura (2021)
The management and disposal of solid waste is currently a global environmental problem, which is why various strategies have emerged to mitigate the impact they generate. Vermicomposting or vermicomposting is one of those biotechnologies used for the transformation of organic matter, mainly using the earthworm as a tool to reduce the volume of the waste, to produce earthworm humus or earthworm as breeding ground, among others. This work contributes to the validation of this technique as an alternative for the use of solid waste: it begins with the characterization of the physicochemical properties of the solid waste obtained in a market place, and the appropriate operating conditions are established for the development of the technique by means of bibliographic referencing.